Educating social entrepreneurs: a proposed framework - Abu Samah , Ainon Jauhariah; Omar, Azura; Ismail, Yusof; Mhd. Sarif, Suhaimi (2015)
Social entrepreneurship dated ages ago before the term social entrepreneur and a related discipline, called social entrepreneurship became vogue. While the discipline of social entrepreneurship tells us about “what’, the identity of social entrepreneur describes to us, “who”. But how to produce the “who” that performs the “what”? This paper draws upon the literature on entrepreneurship education to provide a framework on the education program for social entrepreneurs. Specifically, entrepreneurship education is hypothesized to have a positive influence in creating social entrepreneurs. Having lecturers who have a favourable view towards entrepreneurship and being in contact with practicing social entrepreneurs through the education process is likely to increase the tendency of a student to become a social entrepreneur. Moreover, repetitive emphasis of concepts and knowledge that one receives through formal education, according to the Theory of School Learning and Bloom Mastery Learning, helps in building skill and cognitive ability and one’s perception of his or her own capability to control certain act. Hence, an entrepreneurship education that aims to create social entrepreneurs must be planned in such a way that students are continuously exposed to the rigour of social entrepreneurship. The authors provide their rationale of the elements of education that may be emphasized or deemphasized in educating social entrepreneurs as opposed to business entrepreneurs. By referring to the initial thoughts of the framework, the authors hope that prospective and current facilitators of social entrepreneurship education can adapt their current and future plans in relations to the student background and the infrastructure available.